Manajemen kepala Madrasah Ibtidaiyah dalam menumbuhkan pendidikan karakter religius pada era digital - Murni Yanto (Jurnal Konseling dan Pendidikan, 2020)
This study aims to determine how the management of madrasah principals in fostering religious character education in the digital era. This study uses a qualitative method. The principal of State Islamic Elementary School 1 in Dusun Curup, Rejang Lebong Regency is the main sample in this study, the data collection technique uses the interview method, observation and documentation, the data analysis of the research results uses the reduction technique, triangulation and the conclusion of the research data. Based on this research, it is concluded that the management of the head of State Islamic Elementary School in fostering religious character education in the digital era by leading to the psychological side of students which has implications for behavior, character building in children is carried out in order to create students who have good knowledge and behavior. The character of State Islamic Elementary School students has values that come from Pancasila, religion, culture, and national education goals, namely honest, tolerance, religious, discipline, cooperation, creative, democracy, independence, national spirit, curiosity, love for the country, friendly, communicative, respect for achievement, love peace, care for the environment, love to read, care about socially, and have responsibility. Students' religiosity is shown by obedient attitude or behavior in carrying out the religious teachings that have been adhered to, being tolerant of the implementation of religious worship and living in harmony with followers of other religions. The results showed that the management of the head of State Islamic Elementary School in fostering religious character education had gone well by planning, organizing, implementing and evaluating it very well. Information technology helps facilitate all human activities, information retrieval, convey information and literacy about the addition of knowledge in learning by utilizing technology, so that students can learn by making maximum use of learning resources.